Implementation of Deep Learning through Cross-Subject Collaboration in the Crop Agribusiness Expertise Program: A Qualitative Study in Barru Regency - Besse Sri Muliani; Jamaluddin Jamaluddin; Muhammad Rais (Jurnal Pendidikan Terapan, 2026)
Learning in Vocational High Schools (SMK) still faces challenges in integrating general and productive subjects, resulting in partial learning and not fully providing meaningful learning experiences. This study aims to explore the implementation of in-depth learning through cross-subject collaboration in the Plant Agribusiness Expertise Program at SMK Negeri 4 Barru and SMKS Islam Pesantren Alam Indonesia, Barru Regency. The study used an exploratory qualitative approach and was conducted from October 2025 to March 2026. Twenty-eight informants, consisting of two principals, 12 teachers, and 14 students, were selected purposively. Data were collected through participant observation, in-depth interviews, and documentation studies, then analyzed using the interactive model of Miles, Huberman, and Saldaña through data condensation, data presentation, and drawing and verifying conclusions. The results of the study show four main findings. First, in-depth learning is implemented through collaboration between productive subjects with Mathematics, Indonesian, and English in project-based learning. Second, students are actively involved in every stage of learning, from project planning to presentation of results. Third, teacher competence and collaboration, principal support, student motivation, and the utilization of the learning environment are supporting factors, while limited facilities and infrastructure, time allocation, and the preparedness of some teachers are inhibiting factors. Fourth, the implementation of immersive learning results in a conscious, meaningful, and enjoyable learning experience and develops students' critical thinking, communication, collaboration, creativity, and independence skills. These findings provide an empirical contribution to the development of immersive learning in vocational education.